The impact of COVID-19 infection on thyroid function: COVID-19 and thyroid function - Esraah Alharris; Saleh, Dina; Ali, Thair Wali (Cellular and Molecular Biology, 2025)
Extensive research on COVID-19 has revealed a notable link between the disease and thyroid disorders, highlighting complex interactions between thyroid hormones, immunomodulatory signaling molecules within the thyroid gland, and viral infections. This study evaluated the relationship between thyroid function and COVID-19 in Iraqi patients at Adiwaniyah Teaching Hospital. The cohort for this investigation comprised all patients who were admitted to the isolation center at the Teaching Hospital during the timeframe extending from January 2024 to June 2024. Each participant included in this research underwent comprehensive evaluations of their thyroid function, which is composed of the measurement of thyroid-stimulating hormone (TSH), total triiodothyronine (T3), and serum total thyroxine (T4) levels. Results showed that the serum T4 levels in all participants included in the study were observed to range from 20 to 182 (ng/dl), with the average concentration recorded at 87.26 ± 38.29 (ng/dl); no statistically significant disparity was noted in the mean serum T4 levels relative to the severity of the disease (p = 0.291). The serum TSH levels across all enrolled individuals spanned from 0.03 to 82 (mU/L), with a mean concentration of 5.55 ± 12.36 (mU/L); similarly, there was no statistically significant difference in the mean serum TSH levels when assessed against the disease severity (p = 0.926). According to the serum thyroid hormone concentrations, the cohort was stratified into 17 (24.6%) individuals classified as hypothyroid, 34 (49.3%) categorized as euthyroid, and 18 (26.1%) identified as hyperthyroid. Furthermore, no significant correlation was identified between the disease's severity and the participants' thyroid status (p = 0.556). In conclusion, patients with COVID-19 are liable to develop thyroid function abnormalities that may explain several of the long-term symptoms associated with the disease.